Education What Does Saying That 'Programming Is Hard' Really Say, and About Whom? Shifting the focus from the perceived difficulty of learning programming to making programming more universally accessible. - Becker, Brett A. (Communications of the ACM, 2021)
The article discusses messaging concerning the relative difficulty of learning computer programming with the goal of making computer programming education more accessible. It examines the reinforcement of the difficulty of computer programming in classrooms, workplaces, and the media, the intentional or unintentional stances of high technology companies with respect to the difficulty of programming, and the need to reexamine educational practices concerning computer programming teaching and learning.